2015
DOI: 10.1634/theoncologist.2014-0354
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Single-Agent Pemetrexed in Platinum-Resistant Advanced Urothelial Carcinoma: A Large Single-Institution Experience

Abstract: Background. Pemetrexed is a commonly used treatment for platinum-resistant advanced urothelial carcinoma (UC) based on objective response rates of 8% and 28% in two small phase II studies. To address the discrepancy in reported response rates and to assess efficacy and toxicity outside of a clinical trial setting, we performed a large retrospective analysis of pemetrexed use at Memorial Sloan Kettering Cancer Center. We also investigated candidate prognostic factors for overall survival in this setting to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Therefore, 139 remaining studies were further evaluated for eligibility, and 118 studies were further excluded because they were animal studies, had no survival data with the pretreatment NLR, were without sufficient data to extract the HRs and 95% confidence intervals (CIs), used a continuous variable as the cut-off value, or had overlapping patients or < 10 patients. A total of 21 studies were finally included in this pooled analysis, of which 17 studies included 11, 262 bladder cancer patients treated with RC or TURBT [15-17, 28-41] and 4 studies involved 862 mUC or uUC patients treated with systemic chemotherapy [42-45]. The flow diagram for the study selection process is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, 139 remaining studies were further evaluated for eligibility, and 118 studies were further excluded because they were animal studies, had no survival data with the pretreatment NLR, were without sufficient data to extract the HRs and 95% confidence intervals (CIs), used a continuous variable as the cut-off value, or had overlapping patients or < 10 patients. A total of 21 studies were finally included in this pooled analysis, of which 17 studies included 11, 262 bladder cancer patients treated with RC or TURBT [15-17, 28-41] and 4 studies involved 862 mUC or uUC patients treated with systemic chemotherapy [42-45]. The flow diagram for the study selection process is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic role of the pretreatment NLR regarding RFS, PFS and disease-specific survival/cancer-specific survival (DSS/CSS) in bladder cancer patients was evaluated in 9, 7 and 9 studies, respectively. Of the 21 included studies, Hermanns’s study reported adjusted HRs and 95% CIs [29], while 3 studies reported HRs and 95% CIs derived only from a univariate analysis [42, 44, 45]; the remaining studies presented HRs and 95% CIs obtained by a multivariate analysis. With regard to the quality assessment of the included studies, the Newcastle-Ottawa Scale (NOS) scores ranged from 6 to 8.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal information regarding prognostic factors can help riskstratify patients, tailor monitoring strategies, and interpret and design clinical trials.The study by Bambury et al [5] also examined prognostic factors and suggests a prognostic impact for the neutrophil-lymphocyte ratio (NLR), which has been shown to be prognosticacrossmalignancies [16].Morerecently,aretrospective analysis of prospective trials externally validated the independent prognostic impact of hypoalbuminemia after controlling for the four recognized factors [17]. However, neutrophil and platelet counts, as well as NLR, could not be externally validated in this study.Thus, this five-factor salvage prognostic model (PS, Hb, liver metastasis, time from prior therapy, and hypoalbuminemia) resembles the four-factor first-line prognostic model, which includes anemia, PS, hypoalbuminemia, and visceral metastasis [18].…”
Section: The Value Of Improved Prognostic Classificationmentioning
confidence: 97%